PRODUCTIVITY OF FODDER BEET (BETA VULGARIS L.) UNDER SPRINKLERS IN SALINITY-AFFECTED ARID LANDS OF OMAN - Nadaf, S. K.; Khamisi, S. A. Al; Hag, M. G. El; Lawati, A. H. Al; Akhtar, M. (Emirates Journal of Food and Agriculture, 2017)
Two sets of fodder beet (Beta vulgaris L.) genotypes were evaluated for their productivityand chemical composition in the Sultanate of Oman over different locations and years. The pooled analysis indicated that genotypes of first set were significantly different in fresh fodder yield between the two locations having both soil and irrigation water quality difference, while that of second set of genotypes indicated the absence of any influence in performance over years (74.47 to 76.98 t/ha). The yield levels of fodder beet genotypes at a location having sandy soil with irrigation water of over 5000 ?mhos/ cm (114.99 t/ha) were more than those at another location whose land was also sandy but with irrigation water of about 2000 ?mhos/ cm (86.91 t/ha). The studies on nutrient composition of fodder beet genotypes revealed that fodder beet tubers were rich in starch (NFE =73.0 to 81.0% of DM) forming a good source of carbohydrates. The leaves on the other hand, had more crude protein (8.8 to17.2% of DM) and ash (25.0-33.2% of DM) as compared to the tubers.